Analisis Model Epidemi Penyebaran Tuberkulosis Dengan Struktur Umur - Erna Sari; Asrul Sani; Muh. Kabil Djafar (UIN Imam Bonjol Padang, 2023)
Tuberculosis (TBC) is a contagious disease caused by infection with the bacterium Mycobacterium tuberculosis (Mtb), which attacks the lungs. taking into account the laten period of individuals infected with tuberculosis, this study uses the SEIRS model. The total population is grouped into two age groups, group child and group adult . The purpose of this research is to determine SEIRS model of the spread tuberculosis disease with age structure and its completion behavior. The steps in analyzing of the model can be done by determining the equilibrium point, the results are obtained two equilibrium points, namely disease-free equilibrium points and endemic equilibrium points. Determine basic reproduction number and stability analysis at the equilibrium point. Analysis of the stability of the disease-free equilibrium point is carried out to find the stability of the model using linearization around the equilibrium point. The simulation result are disease-free equilibrium point is the asymptotic stable if the basic reproduction number is less than one, and it means that the disease will disappear over time, and the endemic equilibrium point is stable if the basic reproduction number is more than one, meaning there is disease spread in the population.